Conservation of Sufism Values in the Study of Sufistic Literary Works at the Maulana Rumi Islamic Boarding School - Wahyudi, Heri Fadli; Fajar, Fajar; Kuswandi, Iwan (Universitas Negeri Padang, 2023)
The existence of literature in modern society is often considered and interpreted as a form of imaginative writing, including Sufistic works. If studied more deeply, Sufistic literary works contain Sufistic values worthy of valuable reference materials and reference sources, becoming one of the prides of art in Islam. This type of research is descriptive qualitative, with techniques taken through interviews, observations, and documentation involving caregivers, students, and pilgrims of the Maulana Rumi Islamic Boarding School. Meanwhile, analytical methods are in the form of data reduction, presentation, and inference of data. This study concludes that Sufistic literary works as a medium of learning, entertainment, confidence enhancer, and hope-giver. These four functions are an effort to form a close relationship between God and his creatures.